2022
DOI: 10.1200/jco.2022.40.16_suppl.4003
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and pathological outcome, and pathological regression, in patients receiving perioperative atezolizumab in combination with FLOT chemotherapy versus FLOT alone for resectable esophagogastric adenocarcinoma: Interim results from DANTE, a randomized, multicenter, phase IIb trial of the FLOT-AIO German Gastric Cancer Group and Swiss SAKK.

Abstract: 4003 Background: DANTE evaluates atezolizumab in the perioperative treatment of resectable gastric or gastroesophageal junction (GEJ) adenocarcinoma in combination with FLOT. Here, we report interim results. Methods: DANTE is a multicenter, investigator-initiated, phase IIb trial. Patients (pts) with resectable adenocarcinoma of the stomach and GEJ (≥cT2 and/or N+) were randomized to receive 4+4 cycles of periop. FLOT chemotherapy (arm B) or the same regime with additional atezolizumab at 840 mg, q2w, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 0 publications
3
58
3
2
Order By: Relevance
“…Recently, the randomized DANTE trial reported the interim results of neoadjuvant atezolizumab plus chemotherapy in 146 patients with resectable esophagogastric adenocarcinoma. Compared with our study, DANTE also reported a lower pCR rate (25% in the FAS), but a slightly higher MPR rate (49% in the FAS) 18 . Considering the single-arm design of our study with small sample size, a large-scale randomized controlled trial is warranted to validate camrelizumab plus concurrent chemoradiotherapy in patients with gastric cancer.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Recently, the randomized DANTE trial reported the interim results of neoadjuvant atezolizumab plus chemotherapy in 146 patients with resectable esophagogastric adenocarcinoma. Compared with our study, DANTE also reported a lower pCR rate (25% in the FAS), but a slightly higher MPR rate (49% in the FAS) 18 . Considering the single-arm design of our study with small sample size, a large-scale randomized controlled trial is warranted to validate camrelizumab plus concurrent chemoradiotherapy in patients with gastric cancer.…”
Section: Discussioncontrasting
confidence: 90%
“…The median number of lymph nodes resected was 28 (range, 6-51). The median length of postoperative hospital stay was 8 days (range, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Three patients did not undergo gastrectomy because one had progressive disease, one refused surgery, and one was deemed uncurable due to liver metastases during surgical exploration.…”
Section: Patients' Characteristics and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, for patients who have good to moderate performance status, the suggested perioperative regimen is fluorouracil and oxaliplatin (FOLFOX) or capecitabine and oxaliplatin (CAPOX) [ 13 ]. Ongoing trials are testing the addition of immune checkpoint inhibitors to the FLOT regimen for mismatch repair-deficient tumors that express programmed death-ligand 1, such as pembrolizumab in the KEYNOTE-585 trial [ 102 ], etezolizumab in the DANTE study [ 103 ], and durvalumab [ 104 ]. Moreover, ongoing studies are investigating the addition of trastuzumab to a current chemotherapy regimen in a perioperative setting for patients with ERBB2 (HER2 or HER2/neu)–positive tumors [ 105 ].…”
Section: Non-metastatic Gastric Cancermentioning
confidence: 99%
“…However, the difference was much higher in higher PD-L1 CPS groups as well as the MSI-H subgroup. 44 …”
Section: Gastric/gej Cancermentioning
confidence: 99%